Dose Calibrator Readings due to Radionuclidic Impurities Found in Radiopharmaceuticals - Johnston, A. S.; Colombetti, L. G.; Baker, S. I.; Pinsky, S. M. (Nuklearmedizin - NuclearMedicine, 1980)
The influence of the radionuclidic impurities in radiopharmaceuticals on the reading of sample activities in a dose calibrator has been studied. As a practical example, commercially available 123I was used to measure the effect of radioactive impurities on “dose calibrator” readings. The impurities present in commercially available 123I were identified and quantified by the use of a Ge(Li) detector, and the response of a dose calibrator to each impurity was determined. The contribution of radioactive impurities to sample readings was determined for each sample of 123I studied. It was found that impurities may increase the dose calibrator readings up to 31 %, even though the impurities were within the warranty given by the manufacturer.